PENGARUH METODE PRAKTIKUM BERBANTUAN FLASH TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROKARBON DI KELAS XI IPA SMA MUHAMMADIYAH PONTIANAK - Salmauwati Salmauwati; Muhamad Agus Wibowo; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2016)
ABSTRACTThis study was initiated by the students’ low learning outcomes on Chemistry subject and the teachers’ preference in using lecture method in teaching learning process.This study aimed at 1) finding out the differences of students’ learning outcomes between the use of flash media-assisted practical method and lecture method on hydrocarbon class at grade XI MIA of SMA Muhammadiyah I Pontianak. Using quasi experimental design and Control Group Posttes Design, this study employed the students of grade XI MIA 2 as the samples of experiment group, andthe students of grade XI MIA 2 as the samples of control group. The data collection techniques used were measurement and observation. While the instruments employed were observation sheet and essay. TheU-Mann Whitneytest revealed that the post test score of 0,0140< 0,05 Ho was rejected, while the Ha one was accepted. It means that there was correlation of students’ learning outcomes between the experiment and the control groups. In addition, the effect size result was 1,086 > 0,8 and considered high which indicated the positive effect of flash media-assisted practical method in enhancing students’ learning achievement.Keywords: flash, learning outcomes, hydrocarbon, practical method